Modulating effects of hesperidin on circadian pattern indices of rotenone induced redox homeostasis in clock mutant (cryb) of Drosophila melanogaster. Issue 6 (2nd November 2017) - Manjula, A.; Subashini, R.; Punitha, R.; Subramanian, P.
Abstract: The circadian timing system controls drug metabolism and cellular processes over the 24 h period in every cell. Impaired redox homeostasis is a casual factor for a number of diseases and it is desirable to understand the orchestration of circadian clock under oxidative stress in the model organism, Drosophila melanogaster. This study evaluates the effect of hesperidin on the circadian rhythms of lipid peroxidation products and antioxidants during rotenone-induced oxidative stress in fruit fly. The characteristics of temporal rhythms (acrophase, amplitude, and mesor) of glutathione peroxides (GPx), reduced glutathione (GSH)), were markedly declined in rotenone-treated flies when compared to other groups. Treatment of hesperidin to rotenone-treated flies significantly increased the mesor and modified the amplitudes of antioxidants. Further, delays in acrophase in rotenone-induced flies were reversed by hesperidin treatment. Thus, treatment of hesperidin results in normalization of the altered rhythms of these indices plausibly by its cytoprotective and antioxidant effects. Impairment of 24 h rhythms in oxidative stress markers and antioxidants were observed during rotenone treatment and the impairment is severe in circadian clock mutant cry b flies. A reversibility of rhythms was prominent consequent to hesperidin treatment in wild-type flies than cry b flies. These findings revealed a role of circadian clock in redox homeostasis and the use of Drosophila model in screening putative antioxidative phytomedicines earlier to their use in mammalian systems.